DESIGN OF WALKING ASSISTIVE DEVICE FOR CHILDREN WITH CEREBRAL PALSY, VESTMILES - Budiarti, Agnes; Yuamita, Ferida; Miranda, Suci (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2019)
Celebral Palsy (CP) is a disorder of muscle control which results from some damage to part of the brain. Children with cerebral palsy can have problems such as muscle weakness, awkardness, slowness, shakiness, and difficulty with balance. In severe cerebral palsy, the child may have many difficulties in performing everyday tasks and movements.  However, a proper treatment often brings an improvement, though not a cure. In terms of independent mobility particularly walking and standing, this study aims to design a walking assistive device called Vestmiles. The product design includes four parts: a belt, vest, sandals for parents, and sandals for children with the length and height successively: 47.3 cm and a 23 cm; 39.3 cm and 59 cm; 26.9 cm and 9.9 cm (parents? size of slippers); 23.9 cm and 6 cm (children?s size of slippers). To design the product, it is used the measurement gained from 3 Celebral Palsy children. This work is not only to support physiotherapy program, but also increasing relationship between children and parents. Vestmiles is a user friendly, lightweight, adaptable, efficient and cost effective device.